TINDAK PIDANA PEMERASAN DENGAN ANCAMAN YANG DILAKUKAN OLEH ANAK DI BAWAH UMUR - Hari Subeno (Sekolah Tinggi Ilmu Hukum Awang Long, 2019)
The application of criminal sanctions and actions against children who commit criminal acts of extortion with threats in accordance with the provisions of Article 365 paragraph (1) 1st and 2nd KUHP 1 namely the imposition of criminal sanctions or Article 368 paragraph (1) Jo. Article 55 paragraph (1) paragraph (1) 1st of the Criminal Code, memorizes Article 32 and Article 35 paragraph (1) of Law Number 11 of 2012 concerning Criminal Justice of the Nanak System, as well as other laws and judicial legal considerations in impose criminal sanctions and actions against children who commit criminal acts of extortion by threat is to fulfill all elements of the article in the indictment, as well as witness statements and corresponding statements of defendants coupled with the judge's conviction. In addition, in imposing criminal acts and actions the judge first considers matters that are burdensome and that are mitigating. The Judge's consideration in imposing a criminal offense on a child is to give a deterrent effect to the defendant and so that the defendant does not repeat his actions and to educate the defendant to be aware of his actions, but must pay attention to the rights and needs of the child while serving the sentence. Then the age and consequences of the defendant's actions are one part of the judge's consideration in taking action against the child in the form of a return to parents to be fostered, so that the future defendant can be a better child in all matters and not break the law anymore.